Why "energy price brakes" encourage moral hazard, raise energy prices, and reinforce energy savings - Markus Dertwinkel-Kalt; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
To help households and firms with exploding energy costs in the aftermath of the Ukraine war, a new policy called the "energy price brake" was implemented. A unique feature of this relief measure is that it provides a transfer that increases in the consumer's contractual per-unit price of energy. In a formal model, we show that this policy creates incentives for moral hazard of energy providers to raise per-unit prices. Whereas this moral hazard problem increases the policy's fiscal costs, it also reinforces energy savings. Whether the policy's main beneficiaries are consumers or firms depends on the market structure.
Keywords: D04; L12; Q48; K33; 330; Energy Price Policies; Energy Crisis; Energy Saving; Energy Price Brake